2012
DOI: 10.1371/journal.pone.0045010
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Link between Histone H3 Acetylation and an Increase in the Functional Characteristics of Human ESC/iPSC-Derived Cardiomyocytes

Abstract: Cardiomyocytes (CMs) derived from human embryonic stem cells (hESCs) or human induced pluripotent stem cells (hiPSCs) are functionally heterogeneous, display insufficient biological efficacy and generally possess the electrophysiological properties seen in fetal CMs. However, a homogenous population of hESC/hiPSC-CMs, with properties similar to those of adult human ventricular cells, is required for use in drug cardiotoxicity screening. Unfortunately, despite the requirement for the functional characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…In the present study, cardiomyocytes derived from the TSA ϩ AB group appeared to have a more mature electrophysiological phenotype, being more responsive to ␤-adrenergic and muscarinic agonists and exhibiting better calcium handling compared with cardiomyocytes derived from the control group. This finding is in agreement with a previous study in which TSA was shown to reversibly enhance electrophysiological maturation (shift from hypersensitivity toward more homogeneous and prolonged field potential duration in response to inhibitors of rapid delayed potassium rectifier current, I Kr ) of cardiomyocytes derived from pluripotent stem cells through an increase in histone H3 acetylation [23]. In light of these findings, TSA appears to promote cardiac differentiation of pluripotent stem cells through regulation of cardiac transcription factors, and the optimal treatment protocol needs to be tailored to the cell lines and species involved.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, cardiomyocytes derived from the TSA ϩ AB group appeared to have a more mature electrophysiological phenotype, being more responsive to ␤-adrenergic and muscarinic agonists and exhibiting better calcium handling compared with cardiomyocytes derived from the control group. This finding is in agreement with a previous study in which TSA was shown to reversibly enhance electrophysiological maturation (shift from hypersensitivity toward more homogeneous and prolonged field potential duration in response to inhibitors of rapid delayed potassium rectifier current, I Kr ) of cardiomyocytes derived from pluripotent stem cells through an increase in histone H3 acetylation [23]. In light of these findings, TSA appears to promote cardiac differentiation of pluripotent stem cells through regulation of cardiac transcription factors, and the optimal treatment protocol needs to be tailored to the cell lines and species involved.…”
Section: Discussionsupporting
confidence: 93%
“…For example, 5‐aza‐2′‐deoxycytidine (5′‐azaC), a DNA methyltransferase inhibitor promotes the formation of pluripotent iPSCs and increases the number of ESC‐like cells generation . Additionally, treatment with histone deacetylase inhibitors such as Trichostatin A, valproic acid, or suberoylanilide hydroxamic acid causes a significant increase in histone H3 acetylation and enhances the generation of iPSC colonies . With regard to apoptosis, the high concentration of reactive oxygen species (ROS) induces cellular oxidative stress responses leading to cell senescence and apoptosis and can even lead to necrosis .…”
Section: Introductionmentioning
confidence: 99%
“…We can recapitulate the cardiogenesis during the differentiation from stem cells into cardiomyocytes without changing DNA sequences, and we can investigate and also modify the epigenetic regulation of cardiac development in vitro during these processes. Several studies using stem cell technologies have revealed the relationship between stage-specific epigenetic regulation and stage-specific cardiac gene expression [37,38] , and also succeeded in improving the altered epigenetic regulation and gene expression during cardiac development in vitro by using chemical reagents that modify chromatins [43,46,52,58] . These results suggest that we could treat some congenital heart diseases by using chemical reagents.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies using pluripotent stem cells reported the possibility of this approach. Otsuji et al reported that human ES cell-derived cardiomyocytes in 3D culture demonstrated an increased level of acH3 and increased expression of cardiac-specific genes, such as alpha myosin heavy chain (MYH6), ERG1b, and KCNQ1, compared with those in adhesion culture [46] . They also reported that trichostatin A (TSA), a selective inhibitor of the class I and ІI mammalian HDAC families [47,48] , significantly upregulated the acH3 level of human ES cell-derived cardiomyocytes compared with that of dimethyl sulfoxide (DMSO)-treated controls.…”
Section: The Possibility Of Improving Epigenetic Regulation During Camentioning
confidence: 99%